Configurações literárias do homoerotismo: o jornal Lampião da Esquina (1978-1981) e a construção de subjetividades homoeróticas no Brasil contemporâneo - FAUSTINO, Natanael Araújo (2022)
The aim of this dissertation is to explore the literary heterogeneity and the discursive economy of the newspaper Lampião da Esquina, a periodical published nationally between April 1978 and June 1981, in dealing with homoerotic themes and sub-themes. Inspired by the perspectives opened in the so-called Cultural Studies (BARCELLOS, 2006; PONTES JR, 2014; RAMALHO; RIBEIRO, 1998) and, above all, in Foucauldian studies (FISCHER, 1996; 2015; FOUCAULT, 2014; TANGANELLI, 2019), we are interested in understanding both the social conditions of the newspaper's emergence and the ways in which it explored the boundaries between the literary and the non-literary and how the subjects of discourse, the profiles and senses of homoeroticism were discursively articulated, described and thought about in its literary columns. The option for the notion of homoerotic configurations draws all its pertinence from here to designate a dynamic and non-essentialist process, which takes place in and through language at the very moment it is enunciated (BARCELOS, 1998). Thus, by approaching the 40 editions of Lampião, we seek to understand how different enunciative modes and scenes were constituted there, how the plurality of subjects' voices were technically and discursively organized, constituting a polyphonic discursive architecture that played a decisive role in shaping homoerotic subjectivities in contemporary Brazil.